Women’s perceptions about reducing the frequency of monthly bleeding: results from a multinational survey - Szarewski A; Moeller C (Dove Medical Press, 2013)
Anne Szarewski,1 Cecilia Moeller2 1Centre for Cancer Prevention, Wolfson Institute of Preventive Medicine, Queen Mary University of London, London, United Kingdom; 2Bayer HealthCare Pharmaceuticals, Global Market Research General Medicine, Berlin, Germany Background: Monthly bleeding can have a negative impact on daily life and, given the choice, many women would reduce the frequency of bleeding. While some women choose to occasionally postpone or reduce bleeding frequency with an oral contraceptive (OC), most women have no or limited experience of regularly reducing the frequency of scheduled bleeding with OCs, ie, the extended OC regimen. Study design: An online survey of 4039 women aged 15–49 years who were currently using, had used, or would consider using any form of hormonal contraception was conducted in Brazil, Canada, Czech Republic, France, Germany, Italy, UK, and USA to assess awareness of and the reasons for and against reducing bleeding frequency. Results: Overall, 51.1% and 30.7% of women surveyed were aware that they could occasionally or regularly reduce bleeding frequency with an OC. Moreover, 27.6% and 9.9% of previous/current OC users had occasionally or regularly reduced bleeding frequency with an OC. The main reasons for reducing bleeding frequency were convenience, physician recommendations, special events, and relief of problems associated with bleeding. Many women mistakenly believed that reducing bleeding frequency would have a negative health impact. Conclusion: Additional efforts are needed to educate women about the possibility and potential health benefits of reducing bleeding frequency and to dispel misconceptions about the use of extended OC regimens. Keywords: extended regimen, menstruation, oral contraceptive, withdrawal bleeding, scheduled bleeding